2000
DOI: 10.1034/j.1600-0749.2000.130108.x
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Cutaneous Melanomas in Camargue‐Type Gray‐Skinned Horses (1): Clinical–Pathological Characterization

Abstract: The clinical and pathological characteristics of cutaneous melanomas occurring in Camargue-type gray-skinned horses are reported. Examination of 83 tumor-bearing horses revealed that the tumors occurred most frequently underneath the tail (93.9%) and at high rates in the peri-anal region (43.0%), the lips (33.0%), and the eyelids (24.0%), but rarely in the vulva (3.8%). Tumorous lesions were characterized by the presence of either hemispheric nodules or large infiltrated plaques, or their combinations. Microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 14 publications
4
63
0
13
Order By: Relevance
“…There are many aspects that differ significantly from human melanoma. One unique trait of EMM seems to be the lack of junctional activity in the grey horse EMM (Fleury et al 2000a, Seltenhammer et al 2003. Another dissimilar characteristic is the responsibility of UV exposure for some mutations causing melanoma in humans, and a further difference between EMM and human malignant melanoma clearly is the aggressiveness of the neoplastic growth.…”
Section: Nature Of Emmmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many aspects that differ significantly from human melanoma. One unique trait of EMM seems to be the lack of junctional activity in the grey horse EMM (Fleury et al 2000a, Seltenhammer et al 2003. Another dissimilar characteristic is the responsibility of UV exposure for some mutations causing melanoma in humans, and a further difference between EMM and human malignant melanoma clearly is the aggressiveness of the neoplastic growth.…”
Section: Nature Of Emmmentioning
confidence: 99%
“…Despite their initially slow invasive growth, they frequently metastasize later (Baker and Leyland 1975, Valentine 1995, Fleury et al 2000a, Smith et al 2002. For further information on clinical signs and conventional therapeutic options, the reader is referred to recent extensive reviews on the matter (Metcalfe et al 2013, Moore et al 2013, Phillips and Lembkke 2013, Cavalleri et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Vostry et al (2012b) studied the occurrence of dermal melanoma within the breed and reported that the white colour in greying white horses, one of the basic colour varieties in breed, is a result of progressive greying that is the loss of coat pigmentation with age. Increased susceptibility to dermal melanoma has been associated with greying of white horses by Fleury et al (2000) and Heizerling et al (2001).…”
Section: Horsesmentioning
confidence: 99%
“…Increased susceptibility to dermal melanoma has been proved in greying white horses (Fleury et al, 2000a;Heizerling et al, 2001). Dermal melanoma usually occurs in a greying white horse at 5-6 years of age (Jeglum, 1999).…”
mentioning
confidence: 99%
“…Horses were older than eight years in all cases. Typical sites of melanoma occurrence in white horses are the region under the tail, perianal and anal regions, perineal region, udder, prepuce, lips and eyelids and surrounding tissues, and auricles (Fleury et al, 2000a).…”
mentioning
confidence: 99%